Аргонодуговая обработка сварного соединения стали З0ХГСА - Кулик, В.М.; Савицкий, М.М.; Новикова, Д.П.; Васильев, В.Г. (Автоматическая сварка, 2001)
Изучено влияние парметров режима и термического цикла локальной аргонодуговой обработки без расплавления на структуру металла и механические свойства сварного соединения высокопрочной стали. Показано, что в широких пределах скорости обработки дуговые нагревы до температур аустенитизации металла сварного соединения, закалившегося в процессе сварки, обеспечивают повторную закалку, а ниже температур аустенитизации - кратковременный отпуск. После местной аргонодуговой обработки повышается пластичность и ударна вязкость металла сварного соединения, улучшается характер разрушения, уменьшается чувствительность к концентраторам напряжений. Effect of parameters of conditions and thermal cycle of a local argon-arc treatment without melting on changing the metal structure and mechanical properties of the high-strength steel welded joint was studied. It is shown that the arc heating within the wide ranges of treatment speed up to the temperatures of austenization of the welded joint metal, being hardened during welding, causes the repeated hardening, while at the temperatures below the austenization temperatures a short-time tempering is occurred. After the local argon-arc treatment the ductility and impact strength of the welded joint metal are increased, the mode of fracture is improved, the sensitivity to stress raisers is decreased.